PENERAPAN METODE VAKT DALAM MENGENAL HURUF HIJAIYAH BAGI ANAK TUNARUNGU : Metode VAKT, Siswa, Pendidikan, Strategi. - Panambaian, Tubagus (IAI DARUL ULUM KANDANGAN, 2024)
This study aims to explore the potential application of the VAKT method (Visual, Auditory, Kinesthetic, and Tactile) in introducing Hijaiyah letters to hearing-impaired students at SLBN Kandangan. A qualitative approach with an intrinsic case study design was employed to delve into this topic. The research subjects were the classroom teachers for hearing-impaired students at the school. Data were collected through interviews and observations and then analyzed to understand the implementation of the VAKT method and its impact on students' learning. Findings reveal that this method utilizes multisensory approaches, such as visuals through pictures and colorful letter cards, auditory cues through pronunciation or lip movements, kinesthetic activities like physical exercises, and tactile experiences using embossed letter materials. The teacher also successfully adapted the method to accommodate the diverse abilities of students, including those with residual hearing, multiple disabilities, or hyperactivity. Furthermore, the VAKT method increased active participation and memory retention of Hijaiyah letters, creating an inclusive, interactive, and meaningful learning experience.